Formation of Cognitive Interests of Children with Special Educational Needs Through Eidetics - Кuzenko Оlexandra; Matsuk, Liudmyla; Adamiv, Maria (Journal of Vasyl Stefanyk Precarpathian National University, 2022)
The article emphasizes that Eidetic is one of the effective methods of forming the cognitive interests of preschool children with special educational needs (SEN). Eidetic methods include chain, acroverbal, pictographic, phonetic associations, the method of loci (based on visual associations), nonverbal associations, paradoxical verbal transformations, enlarged structuring of educational material. Their use helps to transform incomprehensible information into an achievable and understandable form to them. Due to Eidetic, various analyzers are involved in cognitive activity at the same time. The child can see and hear and touch, smell, and even taste. At the same time, children's mastery of new knowledge is based on already well-known images, so Eidetic creates a boundless play space in which children's imagination has a wide field for development. The authors note that a characteristic feature of the cognitive interest of preschool children is a selective focus on interest in phenomena, objects, and environmental processes. For students with special educational needs the subject of cognitive interest, as well as for their peers with normative development, is not the whole environment, but only some of its elements, which are personally relevant, attractive, and valuable. The cognitive interest of preschoolers can be both situational and sustainable. It occurs in the process of performing a certain action but may disappear immediately after its completion. At the same time, with systematic pedagogical support, it can become a relatively stable personal quality of a child with special educational needs. An important positive aspect of the use of Eidetic in working with preschool children with SEN is that it creates a psychological situation of success, activates the neurodynamics of brain activity. As a result, the problem areas of the central nervous system and children's deviant behavior are corrected. Eidetic performs a dual developmental and educational function. Due to its application, such mental processes of personality as attention, imagination, memory, different types of thinking are developed, and thus the mastery of educational material is activated. Thanks to the methods of Eidetic, all the child's analyzers are involved, which allows him/her to see, hear, touch, smell, taste, and perceive something new and unknown through the channels of learning about the surrounding reality available to the child with SEN.